Assessment of learning in Youth and Adult Education - EJA: qualitative and quantitative analysis of Brazilian scientific production between 2016 and 2021 (Research, Society and Development, 2023)
This article deals with the evaluation of learning specifically in Youth and Adult Education - EJA. The objective was to qualitatively and quantitatively analyze empirical research that dealt with the evaluation process in the EJA teaching modality. To this end, a survey was carried out in the Digital Bank of Theses and Dissertations - BDTD, in the Theses and Dissertations Catalog of CAPES and SCIELO in the periods from 2016 to 2021. Brazil. The results appreciated that the investigators chose to work with qualitative research and the case study, but there was a predominance of the use of counseling. Regarding the evaluation practices, the use of evaluation as a measuring instrument was not observed, on the contrary, the focus was precisely on evaluating in a formative perspective respecting the specificity of the students.